Abiotic stresses, constraints and improvement strategies in chickpea. Issue 2 (21st January 2014) - Jha, Uday C.; Chaturvedi, Sushil K.; Bohra, Abhishek; Basu, Partha S.; Khan, Muhammad S.; Barh, Debmalya; Varshney, R.
Abstract Chickpea (Cicer arietinum L.) is cultivated mostly in the arid and semi‐arid regions of the world. Climate change will bring new production scenarios as the entire growing area in Indo–Pak subcontinent, major producing area of chickpea, is expected to undergo ecological change, warranting strategic planning for crop breeding and husbandry. Conventional breeding has produced several high‐yielding chickpea genotypes without exploiting its potential yield owing to a number of constraints. Among these, abiotic stresses include drought, salinity, water logging, high temperature and chilling frequently limit growth and productivity of chickpea. The genetic complexity of these abiotic stresses and lack of proper screening techniques and phenotyping techniques and genotype‐by‐environment interaction have further jeopardized the breeding programme of chickpea. Therefore, considering all dispiriting aspects of abiotic stresses, the scientists have to understand the knowledge gap involving the physiological, biochemical and molecular complex network of abiotic stresses mechanism. Above all emerging 'omics' approaches will lead the breeders to mine the 'treasuring genes' from wild donors and tailor a genotype harbouring 'climate resilient' genes to mitigate the challenges in chickpea production.